2019
DOI: 10.1186/s12959-019-0209-5
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulation of platelet adhesion receptors is a controlling mechanism of thrombosis, while also affecting post-transfusion efficacy of stored platelets

Abstract: Physiologically, upon platelet activation, uncontrolled propagation of thrombosis is prevented by regulating mechanisms which affect the expression and function of either platelet adhesion receptors or integrins. Receptor ectodomain shedding is an elective mechanism which is mainly involved in down-regulation of adhesion receptors GPIbα and GPVI. Platelet integrin αIIbβ3 can also be modulated with a calpain-dependent proteolytic cleavage. In addition, activating signals may induce the internalization of expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
43
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 89 publications
1
43
0
Order By: Relevance
“…In addition, we already showed that total adhesion of platelets to collagen is reversely correlated to GPVI shedding [11]. However, it seems that the evaluation of platelet spreading on collagen provides more information about the platelet signaling competence and functional quality beyond that seen for the simple adhesion [50].In addition, since platelet rm adhesion and spreading is mainly mediated by GPVI receptor [1], platelets adhesion area seems to be a better indicator of GPVI competence rather than simple adhesion which might be also modulated by other less important receptors or be affected by artifacts. As presented here, in 5 daysstored PCs, the reduction of platelet spreading on collagen (calculated by platelet surface area) is much more signi cant than simple adhesion loss during storage.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…In addition, we already showed that total adhesion of platelets to collagen is reversely correlated to GPVI shedding [11]. However, it seems that the evaluation of platelet spreading on collagen provides more information about the platelet signaling competence and functional quality beyond that seen for the simple adhesion [50].In addition, since platelet rm adhesion and spreading is mainly mediated by GPVI receptor [1], platelets adhesion area seems to be a better indicator of GPVI competence rather than simple adhesion which might be also modulated by other less important receptors or be affected by artifacts. As presented here, in 5 daysstored PCs, the reduction of platelet spreading on collagen (calculated by platelet surface area) is much more signi cant than simple adhesion loss during storage.…”
Section: Discussionmentioning
confidence: 96%
“…CCCP also showed to signi cantly promote GPVI shedding by ADAM17 rather than ADAM10 which is considered to be the speci c sheddase for GPVI. Given the fact that ADAM 17 activity is modulated by ROS generation [1], the CCCP induced shedding might be also affected by oxidant pathways. Based on these background studies here, for the rst time we showed CCCP-induced ROS generation in platelets that makes a direct link between platelet mitochondrial lesion and induced oxidative stress in an experimental setup.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations